Genetic Structure of Two Protist Species (Myxogastria, Amoebozoa) Suggests Asexual Reproduction in Sexual Amoebae - Fiore-Donno, Anna Maria (Public Library of Science, 2011)
Plasmodial slime molds (Myxogastria or Myxomycetes) are common and widespread unicellular organisms that are commonly assumed to have a sexual life cycle culminating with the formation of often macroscopic fruiting bodies that efficiently disseminate spores. However, laboratory studies based on mating compatibility revealed the coexistence of asexual as well as sexual strains. To test this hypothesis in natural populations, we investigated the genetic variability of two species of the genus Lamproderma. Detailed ecological relevés were carried out in 2007 and 2009 in several deep ravines in the Elbsandsteingebirge (Saxony, south-eastern Germany). Morphological characters of 93 specimens of Lamproderma were recorded and genetic analyses, based on the small subunit ribosomal gene, the internal transcribed spacer 1 and partial elongation factor 1α sequences were carried out for 52 specimens. Genetic analyses showed the existence of two major clades, each composed of several discrete lineages. Most of these lineages were composed of several identical sequences (SSU, ITS 1 and EF-1α) which is explained best by an asexual mode of reproduction. Detrended Correspondence Analysis of morphological characters revealed two morphospecies that corresponded to the two major clades, except for one genotype (Lc6), thus challenging the morphospecies concept. Genetic patterns were not related to the geographical distribution: specimens belonging to the same genotype were found in distinct ravines, suggesting effective long-distance dispersal via spores, except for the Lc6 genotype which was found only in one ravine. Implications for the morphological and biological species concept are discussed.